‘Language has been granted too much power’.1,p.1 Challenging the power of words with time and flexibility in the precommencement stage of research involving those with cognitive impairment - Louise Locock; Deirdre O'Donnell; Sarah Donnelly; Liz Ellis; Thilo Kroll; Éidín Ní Shé; Sara Ryan (Health Expectations, 2022)
Abstract Meaningful and inclusive involvement of all people affected by research in the design, management and dissemination of that research requires skills, time, flexibility and resources. There continue to be research practices that create implicit and explicit exclusion of some members of the public who may be ‘seldom heard’ or ‘frequently ignored’. Our focus is particularly on the involvement of people living with cognitive impairment, including people with one of the many forms of dementia and people with learning disabilities. We reflect especially on issues relating to the precommencement stage of research. We suggest that despite pockets of creative good practice, research culture remains a distinct habitus that continues to privilege cognition and articulacy in numerous ways. We argue that in perpetuating this system, some researchers and the institutions that govern research are committing a form of bureaucratic violence. We call for a reimagining of the models of research governance, funding and processes to incorporate the time and flexibility that are essential for meaningful involved research, particularly at the precommencement stage. Only then will academic health and social science research that is truly collaborative, engaged, accessible and inclusive be commonplace. Public and Patient Contribution This viewpoint article was written by a research network of academics with substantial experience in undertaking and researching patient and public involvement and codesign work with representatives of the public and patients right across the health system. Our work guided the focus of this viewpoint as we reflected on our experiences.